2017
DOI: 10.1155/2017/7548905
|View full text |Cite
|
Sign up to set email alerts
|

Construction Marketing: Developing a Reference Framework

Abstract: Successful companies are strongly committed to marketing management. However, marketing is either misunderstood or completely neglected in many construction companies, mainly due to the difficulty of applying conventional marketing in the industry, accompanied by the lack of sufficient research on the nature of marketing and tailored marketing theories and strategies for the construction. This study attempts to fill a part of this gap by examining the nature of the construction industry from the marketing view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
0
12
0
1
Order By: Relevance
“…Diaphanous volume: DV (axes X, Y, and Z) � DV (6000 mm × 4800 mm × 3000 mm) � 86.42 m 3 Wall frames: (3(F18M) + 1(F6M)) × 2 (parallels to the XZ plane). Beam frames: 5(F48M) (parallels to the YZ plane)…”
Section: Advances In Civil Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Diaphanous volume: DV (axes X, Y, and Z) � DV (6000 mm × 4800 mm × 3000 mm) � 86.42 m 3 Wall frames: (3(F18M) + 1(F6M)) × 2 (parallels to the XZ plane). Beam frames: 5(F48M) (parallels to the YZ plane)…”
Section: Advances In Civil Engineeringmentioning
confidence: 99%
“…ere is currently a global market; therefore, products manufactured in a specific place can be used anywhere in the world. So, if someone intends to design products to be used by consumers in remote places [2], sometimes with different cultures, they will find it really difficult especially if they wish to introduce a customization criterion [3].…”
Section: Introduction To Industrialized Construction Level: Twomentioning
confidence: 99%
“…The use of Grey theory, PROMETHEE, and interval-valued intuitionistic fuzzy sets (IVIFS) in MCDM methods also aids the ranking of contractors [21,23,[28][29][30][31]. MCDM methods have also been used in the selection of cultural heritage buildings [26,[32][33][34]. The most important advantage of multi-criteria methods is their capability to weigh conflicting interests during selection [1].…”
Section: Methods Of Selecting Multi-criteria Decision Making For Contractor Selectionmentioning
confidence: 99%
“…The study that examines the views of construction professionals found out that maintaining a strong pool of professionals to boost a company image was the most widely used among the marketing management strategies. Mokhtariani et al (2017) examined the nature of the construction industry from the marketing viewpoint and developing a comprehensive framework in Iran construction industry.…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%